2005
DOI: 10.5194/angeo-23-1917-2005
|View full text |Cite
|
Sign up to set email alerts
|

Transpolar aurora: time evolution, associated convection patterns, and a possible cause

Abstract: Abstract. We present two event studies illustrating the detailed relationships between plasma convection, field-aligned currents, and polar auroral emissions, as well as illustrating the influence of the Interplanetary Magnetic Field's ycomponent on theta aurora development. The transpolar arc of the theta aurorae moves across the entire polar region and becomes part of the opposite side of the auroral oval. Electric and magnetic field and precipitating particle data are provided by DMSP, while the POLAR UVI i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…It is very likely that processes of merging between the IMF and Earth's magnetic field were involved in their formation (e.g. Blomberg et al, 2005). Sojka et al (1994) proposed the coupled magnetosphereionosphere model that considers a shear Alfvén wave interacting with the ionosphere.…”
Section: Discussionmentioning
confidence: 99%
“…It is very likely that processes of merging between the IMF and Earth's magnetic field were involved in their formation (e.g. Blomberg et al, 2005). Sojka et al (1994) proposed the coupled magnetosphereionosphere model that considers a shear Alfvén wave interacting with the ionosphere.…”
Section: Discussionmentioning
confidence: 99%
“…The emissions are thus likely associated with the currents set up by "lobe reconnection" between interplanetary and open tail lobe field lines, equivalent to the "NBZ currents" that occur at Earth (see Fig. 6 of Blomberg et al, 2005 and Fig. 8 of Belenkaya et al, 2006b), as also suggested by Meredith et al (2014).…”
Section: Auroral Source Locationsmentioning
confidence: 99%
“…The closed field region is contained between the red and green lines, the former being projected from the southern ionosphere and the latter from the northern, which now extends to much greater distances down the tail than for case C. These lines are connected to each other at intersections of the magnetic separator line with the equatorial plane. (For a discussion of the "open" field geometries occurring for northward-and southwarddirected IMF in these cases, corresponding to southward-and northward-directed IMF at Earth due to the differing planetary dipole directions, the reader is referred to the works of Alexeev and Belenkaya (1983) and Blomberg et al (2005), and references therein.) The blue squares again show the equatorial intersections of the equatorward boundary of the dayside oval, which as for case C is somewhat variably located between the outer edge and centre of the ring current region, ∼8.5-12.5 R S .…”
Section: Image a During Southward Imf Conditionsmentioning
confidence: 99%